First Glycoside Hydrolase Family 2 Enzymes from Thermus antranikianii and Thermus brockianus with β-Glucosidase Activity - Schröder, Carola; Blank, Saskia; Antranikian, Garabed (Frontiers in Bioengineering and Biotechnology, 2015)
Two genes tagh2 and tbgh2 coding for enzymes with hydrolytic activity towards esculin were identified from the extreme thermophilic, aerobic bacteria Thermus antranikianii (Ta) and T. brockianus (Tb). Shortened conserved domains predicted a membership of the enzymes of glycoside hydrolase (GH) family 2. At present, β-galactosidase activity is found frequently in GH family 2 but β-glucosidase activity has not been reported in this family before. The enzymes TaGH2 and TbGH2 preferred hydrolysis of nitrophenol-linked β-D-glucopyranosides with specific activities of 3,966 U/mg and 660 U/mg, respectively. Residual activities of 40 % (TaGH2) and 51 % (TbGH2) towards 4-NP-β-D-galactopyranoside were observed. Furthermore, TaGH2 hydrolyzed cellobiose. TbGH2, however, showed no activity on cellobiose or lactose. The enzymes exhibited highest activity at 95 °C (TaGH2) and 90 °C (TbGH2) at pH 6.5. Both enzymes were extremely thermostable and thermal activation up to 250 % was observed at temperatures between 50 and 60 °C. Accordingly, the first thermoactive glycoside hydrolase family 2 enzymes with β glucosidase activity have been identified and characterized. The hydrolysis of cellobiose is a unique property of TaGH2 when compared to the enzymes of GH family 2.